Commercial pectin production from dried florida orange peel: Effect of process conditions on pectin structure and function. Issue 12 (5th October 2022) - Cameron, Randall G.; Ferguson, Kyle; Zhao, Wei; Dorado, Christina
Abstract: To determine the feasibility of using Florida, USA, oranges for pectin production, we evaluated the effects of time, temperature, and pH on pectin properties extracted from dried Valencia orange peel using a hot acid process. Juice extracted peel was collected weekly, and following pretreatment, the dried peel was pooled and used to extract pectin with time (4, 5, and 6 h), temperature (65 and 75°C), and pH (1.6 and 1.8) as process variables. Pectin properties, including yield, sugar composition, molecular weight, intrinsic viscosity, degree of methylesterification, degree of branching, degree of blockiness, absolute degree of blockiness, and Standard Acid in Glass (SAG), were determined. In addition, we evaluated the response of each variable to the process conditions using response surface methodology. The analysis of variance (anova ) models for molecular weight, intrinsic viscosity, and yield were highly significant, with actual values decreasing with increasing temperature. Increasing reaction time also decreased values for molecular weight and intrinsic viscosity. Novelty impact statement: This study indicates that process time and temperature affected pectin quality, functionality, and yield. Increasing temperature had the most detrimental effect on desirability in an optimization analysis.